2016
DOI: 10.1016/j.ifacol.2016.10.335
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Optimal Control Allocation with Mixed Quadratic & Linear Programming Techniques

Abstract: The paper provides a comparison between different control allocation techniques in over-actuated Autonomous Underwater Vehicles. The pseudoinverse, Linear Programming (LP), Quadratic Programming (QP), Mixed Integer Linear Programming (MILP) and Mixed Integer Quadratic Programming (MIQP) are evaluated in simulation on the V-Fides vehicle model. The MILP and MIQP techniques allow to include in their implementations a more detailed characterization of the non-linear static behaviour of the actuators. This customi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In the same reference, some approaches are suggested that appear particularly suitable for spacecraft control allocation problems. Additional references on the subject are: [9], [10], [11], [12] and [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the same reference, some approaches are suggested that appear particularly suitable for spacecraft control allocation problems. Additional references on the subject are: [9], [10], [11], [12] and [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied to re-entry vehicles and UAVs, yielding more accurate control in simulation, but without meeting real-time constraints [45], or without mentioning them [10]. Application to autonomous underwater vehicles, at a low update rate of 10 Hz, has been successful [5].…”
Section: Linearized Control Allocationmentioning
confidence: 99%
“…Control allocation is relevant to many vehicles and has been applied to naval vessels for station keeping [3] and maneuvering [4], underwater vehicle control [5], the electronic stability control of road vehicles [6,7], high-performance aircraft [8,9], and unmanned air vehicles (UAVs) [10,11]. This work aims to provide motivation, derivation, capabilities, and limitations of several commonly used methods, focusing on aircraft.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In active FTC, the typical way to deal with this problem is to use generalized inverses (pseudo-inverses) and a least-squares cost function. 17–19…”
Section: Introductionmentioning
confidence: 99%